Infant abusive head trauma incidence in Queensland, Australia. Issue 2 (31st July 2012) - Kaltner, Melissa; Kenardy, Justin; Le Brocque, Robyne; Page, Andrew
Abstract : This study describes the incidence of head injuries caused by abuse in an Australian infant sample. The frequency of abusive head trauma established by the study is comparable with that reported both internationally and for age-incidence peaks of alternate forms of childhood injury, highlighting the need for investment in prevention initiatives.